Awareness and behavior patterns regarding road safety measures among undergraduate medical students of western Uttar Pradesh: a cross-sectional study - Chaurasiya, Shailendra Kumar; Jain, Pankaj Kumar; Kumar, Sandip; Bajpai, Prashant Kumar; Ali, Nawazish (International Journal Of Community Medicine And Public Health, 2020)
Background: More than 1.2 million deaths occur each year on the world's roads. In India, the number of motor vehicles on the road is increasing with the population and economic growth. It has been estimated that if effective and immediate action is not taken, deaths due to road traffic accidents will become the fifth leading cause of deaths by 2020. Objectives was to assess the level of awareness and behavior regarding road safety rules among undergraduate medical students. Methods: The present cross-sectional study was conducted in a Medical College of western Uttar Pradesh. In the present study 200 final and pre-final year, undergraduate medical students were selected with the help of simple random selection, who drive/use vehicles either of their own or others. The study period was from June 2019 to August 2019. Results: About 29 percent of participants responded that they do not follow lane rules while driving. Study showed that 72.1% and 42.0% were aware that what documents to be carried with them while driving among those who attend and did not attend any program on road safety measures respectively. About 58.1 % and 38.2% were aware that penalty for driving without a helmet can be imposed among those who attend and did not attend any program on road safety measures. Conclusions: Awareness of road safety measures among participants was satisfactory, but the gap was also seen between awareness and behavior patterns regarding road safety measures.